Computed tomography-guided implantation of 125 I seeds brachytherapy for recurrent multiple pulmonary oligometastases: initial experience and results - Li, Jie; Zhang, Lijuan; Xu, Wenhuan; Wang, Teng; Zhou, Leyuan; Xie, Qigen; Wang, Weiguo; Hua, Yanyan (Journal of contemporary brachytherapy, 2017)
To retrospectively evaluate the efficacy and safety of computed tomography (CT)-guided percutaneous interstitial brachytherapy using I radioactive seeds for multiple pulmonary metastatic tumors. Between September 2013 and December 2015, 22 patients with multiple pulmonary metastases, who after conventional chemotherapy and trans-arterial chemoembolization (TACE) therapy were considered unable to withstand stereotactic body radiation therapy (SBRT), received CT-guided I brachytherapy. Clinical data were studied retrospectively. A planning target volume of 90% (D ) was 120-160 Gy for I seeds with an activity of 25.9 MBq. A CT-based evaluation performed 1, 2, and 6 months' post-implantation enabled review of local control of tumors. Twenty-two patients with 65 pulmonary metastases successfully completed treatment. The mean value for D for implantation for I seeds was 132 Gy. Complete response (CR) + partial response (PR) was documented in 81.54%, 78.46%, and 78.46% of patients at 1, 2, and 6 months after implantation, respectively. Fourteen out of 22 patients had CR, 3 had PR, 2 had stable disease (SD), and 3 had progressive disease (PD). Most of the metastases (CR + PR + SD; 87.69% after 6 months) were controlled by implantation. CT-guided I brachytherapy is a safe and effective treatment for multiple pulmonary metastatic tumors, and can achieve good short-term local control, so long as the radiation dose is sufficient.